QUALITATIVE ANALYSIS OF PHYSICAL EDUCATION ITEMS VIA NATIONAL EXAM OF UPPER SECONDARY EDUCATION DESCRIPTORS - Pontes, Jose Airton F.; Silva, Ana Gessica; Sousa, Leandro A.; Martins, Raphaell M. [UNESP]; Almeida, Leandro S. (Centro Federal Educacao Tecnologica Rio Grande Norte, 2017)
Physical Education has been present on National Exam of Upper Secondary Education (ENEM) since 2009 in Languages, Codes and its Technologies area. Taking this into account, the research evaluated and classified the Physical Education items at ENEM regarding the skills of Competency 3 from the exam Reference Matrix. The valid tests from 2009 to 2015 have been analyzed, in which 19 items were identified, whereas 6, 8 and 5 items refer to skills H9, H10 and H11, respectively. Through these analysis, it can be observed that the Physical Education items at ENEM contemplate the competence and skills required in its Reference Matrix.
Keywords: Educational Assessment; Physical Education and Training; Knowledge; College Admission Test